Immune Cells Characteristics and Their Prognostic Effects in Exertional Heatstroke Patients: A Retrospective Cohort Study - Ji, Jingjing; Su, Peng; Lin, Wenyi; Ouyang, Leifang; Wang, Conglin; Jia, Jinxin; Liu, Zheying; Liu, Zhifeng (Frontiers in Medicine, 2022)
Background: Exertional heatstroke (EHS) remains a major problem for those take strenuous physical activity. Inflammation and immune dysfunction were crucial to the development of heatstroke. Present study was aimed to investigate the dynamic changes of the immune cells in the EHS patients, and determining their prognostic effect. Methods: This single-center retrospective cohort study collected all patients with EHS admitted to ICU of the General Hospital of Southern Theater Command of PLA from October 2008 to May 2019. The dynamic changes of main immune cell count, including white blood cell (WBC) count, neutrophil count and ratio, monocyte count and ratio, lymphocyte count and ratio were collected. The neutrophil-to-lymphocyte ratios (NLR) were calculated by neutrophil count/lymphocyte count * 100%. The main outcome was 90-day mortality. Results: Total 189 patients were enrolled. For survivors, after 24 hours, the WBC and neutrophil count began to decrease, and they were back to normal in 72 hours. In addition, the counts of lymphocyte were within normal limits all the time. For non-survivors, the WBC and neutrophil count were continuous over normal range and the lymphocyte count and ratio began to decrease after 24 hours, and continuously-low in the following days. Receiver operating characteristic (ROC) curves analysis showed that increased neutrophils and decreased lymphocytes were associated with the poor prognosis of the patients. A prediction model based on immune cell count in EHS patients was constructed, and lymphocyte count was account for the maximum weight. Conclusion: In EHS patients, increased neutrophils and decreased lymphocytes were associated with the poor prognosis. 72-hour lymphocyte count was the most important prognostic factor.